Implementation and Evaluation of Virtual Anticoagulation Clinic Care to Provide Incessant Care During COVID-19 Times in an Indian Tertiary Care Teaching Hospital - Shambu, Sunil Kumar; B, Shyam Prasad Shetty; Gona, Oliver Joel; Desai, Nagaraj; B, Madhu; Madhan, Ramesh; V, Revanth (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND: COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global pandemic disrupting public health services. Telemedicine has emerged as an important tool to deliver care during these situations. Patients receiving Vitamin K antagonists (VKA) require structured monitoring which has posed a challenge during this pandemic. We aimed to evaluate the impact of Virtual anticoagulation clinic (VAC), a Telehealth model on the quality of anticoagulation, adverse events, and patient satisfaction vis-a-vis standard Anticoagulation clinic (ACC) care. MATERIALS AND METHODS: A bidirectional cohort study was conducted in the Department of Cardiology, JSS Hospital, Mysore. 228 patients in the VAC and 274 patients in the ACC fulfilling inclusion criteria were the subjects of the study. Telehealth tools like WhatsApp and telephone were used. Time in therapeutic range (TTR), Percentage of International normalized ratio in range (PINRR), and adverse events were analysed and compared between the VAC group and the ACC group, between pre-COVID and COVID ACC groups, and between the VAC group and the same pre-COVID cohort. Patient satisfaction was assessed by a questionnaire at the end of 8 months. Descriptive statistics were used for the patient characteristics and inferential statistics for the comparisons between pre-VAC and VAC care were applied. RESULTS: The mean TTR was 75.4± 8.9 % and 71.2±13.4 % in the VAC group and ACC group respectively (p<0.001). The mean PINRR was 66.7± 9.4 % and 62.4±10.9 % in the VAC group and ACC group respectively (p<0.001). There was no significant difference in TTR between the VAC group and the same pre-COVID cohort. The TTR differential between the pre-COVID and COVID ACC groups was significant. In either group, no major adverse events were seen. The most common tools used for data exchange were WhatsApp (83%) and SMS (17%). 74% of patients were extremely satisfied with the overall VAC care. CONCLUSIONS: Virtual anticoagulation clinic, a telehealth model can be used as an alternative option to deliver uninterrupted anticoagulation care during pandemic times.